2016
DOI: 10.1590/0004-282x20160143
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal meningitis: clinical and laboratorial characteristics, fatality rate and variables associated with in-hospital mortality

Abstract: Meningococcal meningitis is a public health problem. The aim of this study was to describe the clinical characteristics of patients with meningococcal meningitis, and to identify associated factors with mortality. This was a retrospective study, between 2006 and 2011, at a referral center in São Paulo, Brazil. Logistic regression analysis was used to identify factors associated with mortality. We included 316 patients. The median age was 16 years (IQR: 7–27) and 60% were male. The clinical triad: fever, headac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Risk factors found to be associated with poor prognosis were old age, and inappropriate treatment. The mortality rate increases linearly with increasing age, being highest in elderly patients (51.7%), in contrast to the results of Strelow et al,16 which concluded that age and mortality were independent, but consistent with those of Choi 17…”
Section: Discussionsupporting
confidence: 40%
“…Risk factors found to be associated with poor prognosis were old age, and inappropriate treatment. The mortality rate increases linearly with increasing age, being highest in elderly patients (51.7%), in contrast to the results of Strelow et al,16 which concluded that age and mortality were independent, but consistent with those of Choi 17…”
Section: Discussionsupporting
confidence: 40%
“…We found additional studies specifically reporting on S pneumoniae (113 studies; 24 553 episodes) (eTable 8 in Supplement 1), N meningitidis (75 studies; 100 278 episodes) (eTable 9 in Supplement 1), H influenzae (49 studies; 28 796 episodes) (eTable 10 in Supplement 1), L monocytogenes (15 studies; 985 episodes) (eTable 11 in Supplement 1),…”
Section: Resultsmentioning
confidence: 99%
“…N meningitidis was among the most frequent pathogens in children and adults (250 studies; 274 study periods; 123 830 episodes) (eTable 16 and eFigure 27 in Supplement 1). This sample was dominated by a Nigerian study describing an outbreak in 2009 with more than 50 000 patients . The overall CFR was 8.8% (95% CI, 8.0% to 9.7%) (eFigure 28 in Supplement 1); CFR was 11% (95% CI, 8% to 16%) before 1961 and 7.2% (95% CI, 5.8.% to 8.7%) i...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding subjects with MM, a 20.9% CFR was found in Brazil for 2000-2006 (Vasconcelos et al, 2011) and 5.4% for 2006-2011 (Strelow et al, 2016). Stratifying by age, the MMrelated CFR was lower in children aged 5 years and 5-15 years 2007: NR 2007: NR 2007: NR 2007: NR Nunes et al, 2016 7 (11.9) 2 (3.4) 2 (3.4) 5 (8.5) NR 6.8 5.1% c Tauil et al, 2014 (Brazil) 2005 1993-1996: NR 1993-1996: NR (43) Baethgen et al, 2008 (Brazil) 229 ( 79) 41 (14.1) 18 (6.2) 2 (0.7) NR NR NR Weidlich et al, 2008 (Brazil) NR ( 64) NR ( 18) NR ( 17 Weckx et al, 2017 (Brazil) 1-4 years: 3 (NR) 1-4 years: 2 (NR) 1-4 years: 1 (NR) 5-9 years: 2 (NR) NR NR 1-4 years: 14 h (NR) 5-9 years: 2 (NR) 5-9 years: 1 (NR) 10-14 years: 2 (NR) 5-9 years: 13 h (NR) 10-14 years: 1 (NR) 10-14 years: 5 (NR) (2.8% and 6.6%, respectively), and increased in subjects aged >50 years (22.7%) (Strelow et al, 2016). During a 2012 outbreak of serogroup W in Chile, the CFR was approximately 27% (Valenzuela et al, 2013).…”
Section: Case Fatality Ratementioning
confidence: 99%
“…For MM cases, from 2000 to 2006, serogroup B was more prevalent in Brazil, followed by serogroup C (Vasconcelos et al, 2011). From 2006 to 2011, serogroup C became the most prevalent (Strelow et al, 2016).…”
Section: Serogroup Distributionmentioning
confidence: 99%